Implementasi Peraturan Daerah Nomor 11 Tahun 2018 Tentang Pengelolaan Barang Milik Daerah - Erwin N purnama; Beatus Tambaip; Nur Jalal; Dapot Pardamean Saragih (SOCIETAS, 2023)
The purpose of the study was to find out how the implementation of Regional Regulation Number 11 of 2018 concerning the Management of Regional Property, the problem of assets, especially motor vehicles controlled by users who have moved from the previous Regional Equipment Work Unit to a new office and have not reported these assets. The method used is qualitative descriptive and uses data collection techniques and tools in the form of observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of the research conducted, that the implementation of Regional Regulation Number 11 of 2018 concerning the Management of Regional Property has not gone well. Regarding communication related to the implementation of regional regulations on the management of regional property, there are still annual records that cannot all be detected, making it difficult to find data. In terms of resources, there are still many asset users who are not aware of reporting to the asset field, similarly, the resources actually needed for asset management are still insufficient, there is a lack of archivists as managers of Regional Property records, there are only archivists and staff who do not have archival training. The bureaucratic structure has so far gone well enough that there are no significant problems.